Gambaran Penurunan Kadar Kalium pada Pasien Penyakit Gagal Ginjal Kronis dengan Hiperkalemia yang diterapi Insulin-Dekstrosa: Overview of Potassium Level Decrease in Chronic Kidney Failure Disease Patients with Hyperkalemia treated with Insulin-Dextrose - Irsan Fahmi Almuhtarihan; Putri Teky Wulandari; Didik Hasmono (LPPM Universitas Abdurrab, 2025)
One of the most critical electrolyte imbalances associated with CKD is hyperkalemia. Insulin-dextrose therapy has been recognized for its efficacy in rapidly lowering serum potassium concentrations. One of the critical factors in the effectiveness of this treatment regimen is the dosage of the insulin. This study aims to describe the effect of insulin dose on potassium levels in patients with hyperkalemia. This study is observational with a retrospective method in chronic kidney disease patients who experience hypokalemia in January 2023 to December 2023. The inclusion criteria included all chronic renal failure patients, with or without comorbidities, who received insulin and dextrose therapy. The combination of (Novorapid® 10iu + D40% + Calcium Gluconas 1g)x3 iv and the combination of (Novorapid® 10iu + D40%)x3 iv + Calcium gluconas (3x1g) iv + Calcium Polystyrene Sulfonate (3x5g) po were the most commonly administered combinations of insulin and dextrose with other hyperkalemia drugs. The highest average reduction in potassium levels reached 1.55 mEq/L obtained from the combination (Novorapid 10 iu + dextrose 40%)x4. In general, the higher the number of insulin doses and/or the frequency of insulin will show a greater decrease in potassium levels.